The role of chemokines in atherosclerosis: recent evidence from experimental models and population genetics. - Bursill, C; Channon, K; Greaves, D (2004)
PURPOSE OF REVIEW: Atherosclerosis is an inflammatory disease process. This review discusses the recent genetic evidence from animal models and human populations that highlight the importance of chemokines in atherosclerosis. RECENT FINDINGS: CC-chemokine/CC-chemokine receptors (CCR), including CCR2/ MCP-1 (monocyte chemoattractant protein-1) and CCR5/RANTES (regulated on activation, normal T-cell expressed and secreted), have been shown in animal knockout and transgenic studies to have significant effects on atherosclerotic lesion size and macrophage recruitment. More recently fractalkine (CX3C1) and its receptor (CX3CR1) have emerged as another important pathway in atherosclerosis. For example, fractalkine is present in human atherosclerotic lesions and is able to stimulate platelet activation and adhesion. CX3CR1 is expressed on human aortic smooth muscle cells and CX3CR1/apolipoprotein E double knockout mice have significantly reduced atherosclerotic lesion size and macrophage recruitment. Human population genetic studies have tried to assess the importance of chemokines in human atherosclerosis. Currently, there is conflicting evidence regarding an association between polymorphisms in CCR2/MCP-1 and CCR5/RANTES and coronary artery disease. There is evidence, however, for an association between the fractalkine receptor polymorphism (CX3CR1-I249) and coronary artery disease in both human population and function studies. SUMMARY: Recent transgenic and gene knockout studies in murine models of atherosclerosis have highlighted the importance of chemokines and their receptors in atherosclerosis. Genetic evidence for a role of chemokines and their receptors in human population studies remains under investigation. Identifying chemokine polymorphisms could help to determine pathways that are important in atherosclerosis disease pathology and that may suggest novel therapeutic targets.